ANALISIS PSIKOLOGI SASTRA DALAM KUMPULAN CERPEN TAK JADI MATI KARYA GDE ARYANTHA SOETHAMA - Ni Luh Widia Pradina Sari; I Ketut Sudewa; I Ketut Nama (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
Abstract: The collection of short stories Tak Jadi Mati by Gde Aryantha Soethama was chosen as the object of research because some of the stories contain inner conflicts experienced by the characters. Inner conflict is closely related to one's psychology. Inner conflict occurs in the heart or soul of a story character. In this thesis, the inner conflict of the main character is studied in four of the twelve short stories in the collection Tak Jadi Mati by Gde Aryantha Soethama. The formulation of the problem in this study is, what is the structure of the short story collection Tak Jadi Mati by Gde Aryantha Soethama which includes plot, characterization, and setting, and what is the inner conflict of the main characters in the short story collection Tak Jadi Mati by Gde Aryantha Soethama. The theory used is the structural theory of Robert Stanton and the theory of literary psychology by Kurt Lewin. The method used in data collection is a literature study method with reading, observing, and note-taking techniques. Data selected by Purpose Sampling technique. Then the methods and techniques of data analysis using analytic descriptive method. At the data presentation stage, this study used a descriptive method presented with thesis systematic presentation techniques. The results of the study show that the grooves used in these four short stories are forward plots which consist of an initial, middle, and final section. The characters in these four short stories discuss the character of each character. The main characters of the short story